Importance of cardiovascular disease risk management in patients with type 2 diabetes mellitus - Lorber D (Dove Medical Press, 2014)
Daniel Lorber Division of Endocrinology, New York Hospital Queens, Department of Medicine, Weill Medical College of Cornell University, New York, NY, USA Abstract: Type 2 diabetes mellitus (T2DM) is commonly accompanied by other cardiovascular disease (CVD) risk factors, such as hypertension, obesity, and dyslipidemia. Furthermore, CVD is the most common cause of death in people with T2DM. It is therefore of critical importance to minimize the risk of macrovascular complications by carefully managing modifiable CVD risk factors in patients with T2DM. Therapeutic strategies should include lifestyle and pharmacological interventions targeting hyperglycemia, hypertension, dyslipidemia, obesity, cigarette smoking, physical inactivity, and prothrombotic factors. This article discusses the impact of modifying these CVD risk factors in the context of T2DM; the clinical evidence is summarized, and current guidelines are also discussed. The cardiovascular benefits of smoking cessation, increasing physical activity, and reducing low-density lipoprotein cholesterol and blood pressure are well established. For aspirin therapy, any cardiovascular benefits must be balanced against the associated bleeding risk, with current evidence supporting this strategy only in certain patients who are at increased CVD risk. Although overweight, obesity, and hyperglycemia are clearly associated with increased cardiovascular risk, the effect of their modification on this risk is less well defined by available clinical trial evidence. However, for glucose-lowering drugs, further evidence is expected from several ongoing cardiovascular outcome trials. Taken together, the evidence highlights the value of early intervention and targeting multiple risk factors with both lifestyle and pharmacological strategies to give the best chance of reducing macrovascular complications in the long term. Keywords: cardiovascular risk, hypertension, obesity, dyslipidemia